Preparation of TiCl4 from panzhihua ilmenite concentrate by boiling chlorination - Fuxing Zhu; Shangrun Ma; Zhanshan Ma; Lihua Qi; Weixing Peng; Kaihua Li; Kehui Qiu (Journal of Materials Research and Technology, 2023)
Titanium tetrachloride (TiCl4) is an important raw material for preparing metallic Ti and TiO2. At present, TiCl4 is mainly produced through boiling chlorination and molten salt chlorination. However, the quality of the titanium slag (or rutile) is significantly influenced by the preparation method. The content of Ca and Mg impurities in Panzhihua ilmenite is high, and the titanium slag after smelting is suitable for the production of TiCl4 via molten salt chlorination. However, chlorinated waste salt pollutes the environment, which should be avoided to meet sustainability goals. Herein, a novel process for preparing TiCl4 from Panzhihua ilmenite involving boiling chlorination is proposed. The carbothermal reduction of the ilmenite concentrate, acid leaching separation of the reduced products, and boiling chlorination process were investigated via X-ray diffraction, mineral dissociation analysis, scanning electron microscopy, and energy-dispersive spectroscopy. The reduced products, which are rich in titanium oxycarbide, Ti2O3 and iron, were prepared after reacting at 1550 °C for 3 h. The Fe content in the reduced products was reduced from 37.85 to 3.0 wt % after leaching with 1–5 wt. % hydrochloric acid. The obtained acid insoluble substances were chlorinated at 500 °C for 25 min to prepare TiCl4, resulting in a chlorination rate of 77.4%. The chlorination residue is rich in unchlorinated rutile, which can be recovered by repeating the boiling chlorination process. Therefore, the environmentally friendly boiling chlorination of Panzhihua ilmenite can be used to prepare TiCl4 avoiding the waste of chlorinated salt.